Placental ischemia during pregnancy induces hypertension, cerebral inflammation, and oxidative stress in dams postpartum - Savanna Smith; Jonna Smith; Kylie Jones; Angie Castillo; Natalia Wiemann; Ahfiya Howard; Mark Cunningham (Hypertension in Pregnancy)
Background Preeclampsia (PE) is characterized as de novo hypertension (HTN) with end-organ damage, especially in the brain. PE is hypothesized to be caused by placental ischemia. PE affects ~5–8% of USA pregnancies and increases the risk for HTN and cerebrovascular diseases (CVD) later in life. We hypothesize that blood pressure (BP), cerebral oxidative stress, and cerebral inflammation will increase in postpartum (PP) placental ischemic dams.Methods Placental ischemia was induced in pregnant Sprague Dawley dams, utilizing reduced uterine perfusion pressure (RUPP) surgery. At 6 weeks PP (~3 human years), BP was measured via carotid catheterization, and cerebral oxidative stress and inflammation were assessed via ELISAs, biochemical assays, and Western blots.Results BP, cerebral pro-inflammatory cytokines (TNF-α and IL-6), and GFAP (a marker of astrocyte activity) were increased in PP RUPP dams. Cerebral hydrogen peroxide (H2O2) was also increased in PP RUPP dams, and had a strong correlation with PP RUPP BP, proinflammatory cytokines (TNF- α and IL-6), and GFAP astrocyte activation.Conclusion PP RUPP dams have increased BP, cerebral oxidative stress, and cerebral inflammation at 6 weeks postpartum. These changes in cerebral inflammation and oxidative stress may contribute to the pathology and development of HTN and CVDs in postpartum dams.